Aneuploidy in children with relapsed B‐cell precursor acute lymphoblastic leukaemia: clinical importance of detecting a hypodiploid origin of relapse. (3rd February 2019) - Groeneveld‐Krentz, Stefanie; Schroeder, Michael P.; Reiter, Michael; Pogodzinski, Malwine J.; Pimentel‐Gutiérrez, Helia J.; Vagkopoulou, Renia; Hof, Jana; Chen‐Santel, Christiane; Nebral, Karin; Bradtke, Jutta; Türkmen, Seval; Baldus, Claudia D.; et al.
Summary: Aneuploidy is common in paediatric B‐cell precursor acute lymphoblastic leukaemia (ALL). Specific subgroups, such as high hyperdiploidy (>50 chromosomes or DNA Index ≥1·16) and hypodiploidy (<45 chromosomes), predict outcome of patients after primary treatment. Whether aneuploidy has a prognostic value for relapsed disease is yet to be determined. Using DNA index and centromere screening by multiplex ligation‐dependent probe amplification, we investigated aneuploidy in 413 children treated for first relapse of B‐cell precursor ALL according to the ALL‐REZ BFM 2002 protocol. Ten‐year event‐free survival of patients with high hyperdiploid relapses approached 70%, whereas it was only 40% in low hyperdiploid relapses. Three patients with apparent hyperdiploid relapse had TP53 mutations. In these cases, array‐based allelotyping revealed a hypodiploid origin with absence of the hypodiploid founder clone (masked hypodiploidy). Collectively, patients with evident or masked hypodiploid relapses showed an extremely low event‐free survival rate of 9%. Importantly, the current relapse risk stratification did not identify cases with masked hypodiploidy as high‐risk patients, due to their favourable clinical presentation. In multivariate analysis, hypodiploidy proved to be an independent prognostic factor. This finding supports stratification of relapses with hypodiploid origin into high‐risk arms in future trials or allocation of patients to alternative treatment approaches.